Mobile and online learning journal : effects on apprentices' reflection in vocational education and training - Mauroux, Laetitia [Verfasser]; Könings, Karen D. [Verfasser]; Dehler Zufferey, Jessica [Verfasser]; Gurtner, Jean-Luc [Verfasser] (My University, 2014)
"While learning journals (LJs) have been shown to support self-regulated learning strategies, reflection and learning outcomes in academic contexts, few studies have investigated their relevance in vocational education. A mobile and online learning journal (MOLJ) was developed to support reflection on workplace experiences. However, acceptance of the mobile and online learning journal by apprentices and supervisors is not trivial. This study investigated how apprentices use the mobile and online learning journal and why they use it that way. The mobile and online learning journal was developed for apprentices in the field of bakery and contains a recipe book, a smartphone app to take pictures of workplace experiences, and a learning journal for reflection. Apprentices' workplace supervisors have access to the mobile and online learning journal to provide support and feedback. A mixed method study was conducted with 16 apprentices from the French speaking part of Switzerland. Indicators of their use of the mobile and online learning journal were recorded, while reasons for use were studied by questionnaires and semi-structured interviews. Four kinds of users of the mobile and online learning journal were identified: Multifunction users, picture takers, learning journal users, and overall low users. The most determining factors for the acceptance and use of the mobile and online learning journal by apprentices were their interest in the use of a smartphone at the workplace, their acceptance of reflection on workplace experiences through the mobile and online learning journal, and supervisors' participation and provision of feedback. Promoting the use of learning journals by apprentices requires strong guidance in the design of the learning journal as well as support and feedback from supervisors." (Authors' abstract, BIBB-Doku)
Keywords: L 4.2.3 Internetbasiertes Lernen / E-Learning; L 2.1.3 Erfahrungslernen; S 1.3 Berufliche Erstausbildung; I 2.2.1 Westeuropa; Lehr-Lern-Forschung; E-Learning; Mobiles Lernen; Lernen am Arbeitsplatz; Reflexion; Berufsausbildung; Bäcker; Empirische Untersuchung; Schweiz